Analysis Of Practicum Implementation In Growing Psychomotoric Students Online Biology Subjects - Indayana Febriani Tanjung; Rohani Rohani; Syahdina Putri (Journal of Education and Teaching Learning, 2022)
This study aims to determine the implementation of practicum in developing students' psychomotor in biology subjects online at MTs PAB 2 Sampali. The method used in this research descriptive quantitative method. The population and sample this study were class IX students, totaling 32 students. Data collection techniques used in the form (1) observation used to obtain data on student performance when doing practicum, which was assessed to include students' psychomotor skills before the practicum, implementation during the experiment, and the end of the practicum activity, (2) documentation, used to add completeness of research information. From the results of the study, it was shown that in the implementation of the online practicum it succeeded in growing students' psychomotor, in the grafting practicum at the imitation and manipulation stage it had a good category with an average value 82.25% and 81.97%, accuracy and articulation stage it had a very good category. both at the average value 90.87% and 90.93%, naturalization stage it has a fairly good category with an average value 70.62%. In the implementation of the practicum, the stages of imitation, manipulation and articulation have good categories with an average value 85.63, 83.95%, and 87.5%, in the accuracy and naturalization stages have a very good category with an average value 96.12%. In the implementation of the ducking practicum at the imitation and accuracy stage, the category is very good with an average value of 90.93% and 93.43%, the manipulation, articulation and naturalization stages have a good category with an average value of 78.69%, 83.75%, and 82.5%.